Staphylococcus aureus in Traditional Coconut milk Drinks - Putri Mustika Sari; Ahmad Muhlisin (Baiman Bauntung Batuah Center, 2019)
Coconut milk is a food ingredient that is used to increase the taste of food and drinks. Coconut milk has processed products in the form of traditional drinks such as ice dawet and cendol ice. According to the Indonesian National Standard in 2009 about Maximum Microbial Contamination in Food in liquid coconut milk must be in accordance with the requirements of TPC parameters, MPN Coliform, Salmonella sp., and Staphylococcus aureus. This study aims to determine the description of Staphylococcus aureus contamination in traditional coconut milk in the Banjarbaru region. This type of research is a descriptive survey. The samples in this study were traditional drinks (es dawet and es cendol) that used coconut milk by using Purposive sampling techniques as many as 6 sellers who made 2 times taking, namely taking 1 hour (testing I) after processing and 2 hours after the first take (testing II) . From the research that has been done, it is found that there are 4 samples of Staphylococcus aureus contamination in 4 samples, namely 3 samples fulfilling the requirements of the Indonesian National Standard and 1 sample that does not meet the requirements of the Indonesian National Standard. It is expected for the seller to always maintain personal hygiene, pay attention to the cleanliness of drinks sold either during processing or serving, noting the cleanliness of the appliance and storing the ingredients of the drinks sold.